Accounting for Managerial Control: An Application of Chance-Constrained Programming - Gonedes, Nicholas J. (Journal of Accounting Research, 1970)
An important function of managerial accounting is the provision of information for controlling activities. In this regard, the data generated by the accounting process should facilitate: (1) evaluations of the degree of conformance between actual states of affairs and goals, (2) the selection of managerial actions that will contribute to the conformance of actualities and goals, and (3) evaluations of the need for exploratory efforts directed towards developing additional alternative actions, modifying managerial goals, or both. Several proposals have appeared which are designed to enhance the degree to which the accounting process facilitates managerial control. Most of these proposals focus upon two actions that may be initiated in order to a particular process, i.e., investigate or do not investigate. Also, most of these proposals only consider a probability distribution defined on the current state of the system (and, usually, conditional upon a set of observations or experimental outcomes).' Optimal action is defined by some of the proposed approaches by comparing a measurable characteristic of the process to be controlled with a stipulated managerial goal or a stipulated standard. Simple control chart schemes and schemes that embrace the use of information-theory measures are examples of such ap-